Contextual, Individual or Group Influences on Hesitancy towards COVID-19 Vaccination: A Descriptive Study (Journal of Pharmaceutical Negative Results, 2023)
The global pandemic of coronavirus disease 2019 (COVID-19) has infected more than 257 million population and out of them, 5.1 million already died [1][2][3]. Both therapeutic and non-therapeutic measures were taken to flatten the number of COVID-19 confirmed cases and reduce deaths [4]. Vaccines aside from COVID-19 are one of the foremost effective and reliable public health interventions ever implemented that prevent many deaths from viral infections per annum[5][6]. The SAGE working party on Vaccine Hesitancy concluded that Vaccine hesitancy refers to a delay in acceptance or refusal of vaccination despite the availability of vaccination services [7]. The hesitancy regarding COVID-19 vaccines is prominently evident worldwide [8]. Studies have identified several factors related to COVID-19 vaccine hesitancy in several domains [9]. The identified factors included various socioeconomic and demographic characteristics[10] (e.g., age, sex, residence, income, occupation, and marital status) constructs of the health belief model, constructs of theory of planned behavior, and therefore the 5c psychological antecedents[11][12], vaccines-related knowledge[13], attitude towards COVID-19 vaccination, conspiracy beliefs, trust and confidence[14], COVID-19 preventive behavioral practices[15], and therefore the perceived safety and side effects of the vaccines. Despite vaccine hesitancy, the demand for vaccines increases over time, and disparities in vaccine access within and across the countries are remarkable [16]. Albeit the first drivers of vaccine hesitancy are often context-specific [17], there are some agreements that confidence and trust in the COVID-19 vaccine play a critical role in increasing vaccine acceptance[18]. Hesitancy for being get vaccinated was measured with the concept including contextual, group, or individual factors which were again subdivided into the aspects of barriers to vaccination, etc. [19][20].